2018
DOI: 10.1016/j.anbehav.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees gesture to humans in mirrors: using reflection to dissociate seeing from line of gaze

Abstract: There is much experimental evidence suggesting that chimpanzees understand that others see. However, previous research has never experimentally ruled out the alternative explanation that chimpanzees are just responding to the geometric cue of 'direct line of gaze', the observable correlate of seeing in others. Here, we sought to resolve this ambiguity by dissociating seeing from direct line of gaze using a mirror. We investigated the frequency of chimpanzees' visual gestures towards a human experimenter who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Particularly, in the case of this study, rather than attributing their own inner experience to the actor, it is possible that apes learned about the psychological affordances of the barriers and used this information to determine whether the actor had an unobstructed line of sight (but see ref. 44 for recent evidence against this possibility in a different research paradigm). Moreover, to determine whether apes represent agents' beliefs or belief-like states, it will be necessary to investigate their ability to anticipate an agent's action based on false beliefs about object identity.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, in the case of this study, rather than attributing their own inner experience to the actor, it is possible that apes learned about the psychological affordances of the barriers and used this information to determine whether the actor had an unobstructed line of sight (but see ref. 44 for recent evidence against this possibility in a different research paradigm). Moreover, to determine whether apes represent agents' beliefs or belief-like states, it will be necessary to investigate their ability to anticipate an agent's action based on false beliefs about object identity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work, for example, showed that chimpanzees gesture more when a human with food has a “‘direct line of gaze” to them (i.e., when he is facing them) than when he does not (Gómez, ; Hostetter et al, ; Kaminski et al, ; Leavens et al, ; Liebal et al, ; Povinelli & Eddy, ; Povinelli et al, ; Tomasello et al, ). To dissociate “line of gaze” from seeing, Lurz et al () adjusted the task so that in some conditions the experimenter faced away from the subject (i.e., there was no “line of gaze”) but could still see her through a mirror. As predicted by the mentalistic hypothesis, they found that chimpanzees gestured more in all conditions in which the experimenter could actually see them than in those conditions in which she could not, independent of whether the experimenter actually had a “line of gaze” to the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…In each of these studies regardless of whether the dependent measure was looking behavior (Drayton & Santos, 2018;Marticorena et al, 2011;Martin & Santos, 2014) or object-choice/reaching behavior (Hare et al, 2001;Kaminski et al, 2008) , when an object was spatially manipulated while an agent could not see it, primates seemed to no longer have any expectations about the agent's knowledge. While it is challenging to entirely rule out low-level explanations for this pattern based on behavior-reading (Lurz, Kanet, & Krachun, 2014;Povinelli & Vonk, 2003), our perspective is that primates do form inferences about the mental states of agents in these studies, as supported by recent experimental work on chimpanzees' understanding of what others can see in the absence of a direct line of gaze (Lurz, Krachun, Mahovetz, Wilson, & Hopkins, 2018).…”
Section: Introductionmentioning
confidence: 92%